-2-9f=5+9-7f

Simple and best practice solution for -2-9f=5+9-7f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-9f=5+9-7f equation:



-2-9f=5+9-7f
We move all terms to the left:
-2-9f-(5+9-7f)=0
We add all the numbers together, and all the variables
-9f-(-7f+14)-2=0
We get rid of parentheses
-9f+7f-14-2=0
We add all the numbers together, and all the variables
-2f-16=0
We move all terms containing f to the left, all other terms to the right
-2f=16
f=16/-2
f=-8

You can always share this solution

See similar equations:

| 3=2x+3x+3 | | v+17?11=65 | | 1.69+2.1k=4.9k-9.38-4K | | X2+6x+30=0 | | -7z-10=10+3z | | -r+10=9r-10 | | 9.78+3.5u=-9.11+0.6u-0.25 | | 2x-(3x-8)=2 | | 8x^2-30x+45=0 | | 8x(2-30x+45=0 | | 7(6x=54) | | 8h+1=10+9h | | Q=1/2p+3 | | 7c+2+10c=-10c+2 | | 2x/2.8=8.2 | | 2t+10=4t-8 | | -10y+9=-7y-5y+9 | | -m+3=m-7 | | 3x+12=3x+25 | | 4x^-3+1=0 | | 6.4g+4=3.4g+10 | | -10d-1+3D=-d-1 | | 2.8/x=35 | | 8+f=-5f-10 | | 8-5h=-9h | | 5+8=18(3?x)?5+8=18 | | 3x+2(-12)=64 | | -4.1=8.7+y/8 | | 4x+14=5x+4=6x-3 | | -4.1=8.7=y/8 | | 2l+8=12 | | 77-3a=44 |

Equations solver categories